Geographical clustering and the effectiveness of public innovation programs - Dirk Crass; Christian Rammer; Birgit Aschhoff (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
The paper analyzes how geographical clustering of beneficiaries might affect the effectiveness of public innovation support programs. The geographical proximity of firms operating in the same industry or field of technology is expected to facilitate innovation through knowledge spillovers and other localization advantages. Public innovation support programs may leverage these advantages by focusing on firms that operate in a cluster. We investigate this link using data from a large German program that co-funds R&D projects of SMEs in key technology areas called 'Innovative SMEs'. We employ three alternative cluster measures which capture industry, technology and knowledge dimensions of clusters. Regardless of the measure, firms located in a geographical cluster are more likely to participate in the program. Firms being part of a knowledge-based cluster significantly increases their chance of receiving public financial support. We find no effects, however, of geographical clustering on the program's effectiveness in terms of input or output additionality.
urn:nbn:de:bsz:180-madoc-417642
Keywords: C35; H50; O31; O32; O38; R59; 330; Innovation; Government Policy; Regional Government Analysis